Computers and student learning : bivariate and multivariate evidence on the availability and use of computers at home and at school - Thomas Fuchs; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2004)
We estimate the relationship between students? educational achievement and the availability and use of computers at home and at school in the international student-level PISA database. Bivariate analyses show a positive correlation between student achievement and the availability of computers both at home and at schools. However, once we control extensively for family background and school characteristics, the relationship gets negative for home computers and insignificant for school computers. Thus, the mere availability of computers at home seems to distract students from effective learning. But measures of computer use for education and communication at home show a positive conditional relationship with student achievement. The conditional relationship between student achievement and computer and internet use at school has an inverted U-shape, which may reflect either ability bias combined with negative effects of computerized instruction or a low optimal level of computerized instruction.
Keywords: I2; 330; computers at home; computers at school; student achievement; educational production; PISA; Bildungsniveau; Computergestütztes Lernen; Computergestütztes Verfahren; Medienverhalten; Welt; PISA